(untitled) (Eurasian Journal of Media and Communications, 2022)
The emerging polycystic ovary syndrome (PCOS) as the cause of the first signs of menstrual disorders is well known to reproductologists and gynecologists around the world. This term is new, collective, and the pathogenetic aspects of the disease are not fully understood. Its main manifestation is ovarian hyperandrogenism, which is accompanied by a violation of the cycle in combination with structural morphological changes in the ovaries. The article describes new innovative biochemical and hormonal methods for predicting early markers of polycystic ovary syndrome in adolescent girls.